Massive Dentigerous Cyst within the Anterior Part of The Mandible: A Case Report - Rema Hwas; Mohamed Rohuma; Faten Bshena (Khalij-Libya Journal of Dental and Medical Research, 2021)
Dentigerous cysts are the most common developmental odontogenic jaw cysts, associated with crowns of an Unerupted tooth. Usually, they occur in the second and third decade of life with a male predilection. They are frequently asymptomatic and mostly discovered incidentally on routine dental radiographic examination. Its growth is slow, and can reach a considerable size causing bone expansion and displacement of teeth. Mandibular lower third molars are the most frequently effected teeth; dentigerous cysts involving impacted mandibular canines are rarely reported. Surgical enucleation with extraction of the associated tooth is the standard treatment for dentigerous cyst, marsupialization is recommended for large lesions. We report a rare case of a large dentigerous cyst in a 62-year-old male patient, associated with impacted left mandibular canine, extending from the retro-molar area of left side crossing the midline to the 2nd premolar in the other side, that was successfully treated by marsupialization followed by enucleation and removal of the impacted tooth.